Induction of apoptosis by baculovirus transactivator IE1. - Prikhod'ko, E A (1996)
Apoptosis is induced upon infection of SF-21 cells by mutants of the baculovirus Autographa californica nuclear polyhedrosis virus (AcMNPV) lacking a functional p35 gene which encodes a stoichiometric inhibitor of members of the interleukin-1beta converting enzyme family of cysteine proteases (N.J. Bump et al, Science 269:1885-1888, 1995; R.J. Clem, M. Fechheimer, and L.K. Miller, Science 254:1388-1390, 1991). We found that transfection of SF-21 cells with the AcMNPV ie-1 gene was sufficient to induce apoptosis, which was characterized by fragmentation of cellular DNA into oligonucleosomal fragments and apoptotic body formation. No signs of apoptosis were observed in Trichoplusia ni TN-368 cells transfected with ie-1, a result which is consistent with the observation that p35 mutants of AcMNPV do not induce apoptosis in this cell line. Cotransfection of SF-21 cells with p35 blocked ie-1-induced apoptosis, indicating that expression of ie-1 activates apoptosis through a p35-inhibitable cysteine protease pathway. Cotransfection with Cp-iap, an active member of another family of antiapoptotic inhibitors of apoptosis (iaps), also inhibited IE1-induced apoptosis. Thus, ie-1 may participate in inducing apoptosis in AcMNPV-infected cells, although the dependence of induction on DNA replication suggests that ie-1 is not the direct apoptotic signal during infection. The ie-1 gene product, IE1, is known to be a potent transactivator of baculovirus gene expression that interacts with specific palindromic sequences which can act as transcriptional enhancers and as origins of DNA replication in transient assays.